Handbook of development economics / edited by Hollis Chenery and T . N. Srinivasan - Hollis Chenery (ed.); Srinivasan, T.N. (ed.) (New York, 1991)
The aim of the Handbooks in Economics series is to produce Handbooks for various branches of economics, each of which is a definitive source, reference, and teaching supplement for use by professional researchers and advanced graduate students. Each Handbook provides self-contained surveys of the current state of a branch of economics in the form of chapters prepared by leading specialists on various aspects of this branch of economics. These surveys sum marize not only received results but also newer developments, from recent journal articles and discussion papers. Some original material is also included. but the main goal is to provide comprehensive and accessible surveys. The Handbooks are intended to provide not only useful reference volumes for professional collections but also possible supplementary readings for advanced courses for graduate students in economics.
Keywords: Economic development Handbook manual etc